THE QUALITY OF BOILED-FROZEN SHRIMPS REALIZED IN RETAIL TRADE - Olga Mikhailovna Burmistrova; Evgeny Alexandrovich Burmistrov; Natalia Leonidovna Naumova; Elizaveta Alekseevna Pyrkova (Современная наука и инновации)
A comprehensive study of the quality of boiled-frozen shrimps, sold in retail trade, has been carried out. The organoleptic, physico-chemical indices and mineral composition of products were studied, a sensory evaluation was carried out. Violations of the requirements of the current regulatory documents, admitted by both manufacturers of products, and retailers have been detected.